GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 42 species occurrences available in GBIF matching the query: TaxonKey: Ramalina celastri (Spreng.) Krog & Swinscow Country: Paraguay or Uruguay. The dataset includes 42 records from 12 constituent datasets: 2 records from Lichen Herbarium Berlin. 12 records from Arizona State University Lichen Collection. 3 records from Lichen herbarium, Oslo (O). 1 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from Australia's Virtual Herbarium. 3 records from Royal Botanic Garden Edinburgh Herbarium (E). 2 records from Lichen herbarium, UiB. 1 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 11 records from Botany (UPS). 1 records from Natural History Museum (London) Collection Specimens. 4 records from Field Museum of Natural History (Botany) Lichen Collection. 1 records from Australian National Herbarium (CANB).
Keywords: GBIF; biodiversity; species occurrences